An Attentional Blink Research on Different Types of Words in Male with Substance Use Disorder. - Lu, Mengyao; Lian, Chenxin; Zeng, Xiaoqing (International Journal of Mental Health & Addiction, 2024)
Individuals with substance use disorder (SUD) tend to have attention bias to drug and negative emotions, which leads to drug craving and relapse. This study examines attentional bias from the time dimension, and adopts the rapid sequence visual presentation (RSVP) paradigm to study the attentional blink effect of individuals with SUD towards different types of negative words. A total of 55 males with SUD were recruited from a compulsory drug rehabilitation center in Jiangxi Province. The results indicated that the following: (1) The accuracy of T2 recognition when T1 was correctly recognized (T2|T1) increased with the increase of the time interval, indicating that the attentional blink was successfully induced. (2) When T1 was addictive vocabulary, compared with the neutral vocabulary, the attentional blink effect of males with SUD was enhanced. When T2 was negative addiction vocabulary or negative vocabulary, compared with the neutral vocabulary, the attentional blink of males with SUD was weakened. The current research results not only find that males with SUD have an attention bias towards addiction clues from the time characteristics of the attention process, but also it is of great significance to guide the rehabilitation centers to improve the craving and relapse of males with SUD by reducing the appearance of negative addictive information.